Kontribusi Gembala Dalam Mengurangi Kasus Kekerasan Terhadap Anak - Hendrikson Febri (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
Violence against children often occurs in various places, whether at home, school, or in the surrounding environment. Data from the Ministry of Women's Empowerment and Child Protection (KPPPA) shows that from 2015 to 2023, incidents of violence against children have been increasing. The perpetrators of such violence are frequently the children's own parents or acquaintances. Common forms of violence against children include physical abuse, emotional abuse, sexual abuse, neglect, and exploitation. The aim of this research is to explore the role of pastors as a solution to prevent violence against children. This study employs a qualitative descriptive approach based on literature review. The roles of pastors in combating violence against children include providing education and awareness, family counseling, building a caring community, and conducting counseling sessions.